Arthropod Community Structures of Rice Ecosystems in the Philippines - Heong, K.L.; Aquino, G.B.; Barrion, A.T. (Cambridge University Press, 1991)
The arthropod community associated with irrigated rice grown in five sites in Luzon Island, Philippines, was analysed using guild categories. Phytophages and predators were predominant in all sites. The phytophage species were mainly Homoptera and dominated by Nephotettix virescens (Distant), N. nigropictus (Stål) (Cicadellidae), and Nilaparvata lugens (Stål) and Sogatella furcifera (Horváth) (Delphacidae). Predators were mainly Heteroptera with Microvelia douglasi atrolineata Bergoth (Veliidae), Mesovelia vittigera (Horváth) (Mesoveliidae), and Cyrtorhinus lividipennis Reuter (Miridae) as the most abundant species. Spiders were the next dominant group with Pardosa pseudoannulata (Böesenberg and Strand) and three species of Tetragnatha the most common. Differences in species diversity between the sites were easily differentiated using diversity indices. The relative differences in arthropod abundance, species richness and diversity may be attributed to the median temperatures, cropping patterns, and diversity in crop stages and germplasm in the sites. Predator-Homoptera correlations were significant in all cases. High positive correlations were obtained for veliids, spiders and Cyrtorhinus lividipennis, in most sites.